¿Qué se puede esperar en términos políticos y económicos del orden global en 2025? Desafíos y oportunidades: What can be expected in political and economic terms from the global order in 2025? Challenges and opportunities - Villasmil Espinoza, Jorge J. (Political Questions, 2025)
The general purpose of this text is twofold: on the one hand, it is intended to reflect, as an editorial, on what can be expected in political and economic terms from the global order in 2025, with special emphasis on the challenges and opportunities; on the other hand, the text serves as a presentation for the July-December 2024 issue of Volume 42, Number 81 of Cuestiones Políticas. It concludes that the global order in 2025 will be marked by a complex interplay between political and economic challenges. Democratic countries must prepare to navigate an uncertain environment while seeking to seize new opportunities to advance their human rights agendas. The key will be to foster an active and informed citizenry that demands accountability from their leaders.